Does rural livelihood change? Household capital, climate shocks and farm entry-exit decisions in rural Pakistan - Ahmad, Muhammad Irshad; Oxley, Les; Ma, Hengyun; Liu, Ruifeng (Frontiers in Environmental Science, 2023)
Agriculture is a primary source of livelihoods in developing countries. The process of entry and exit of farming activities continues to play an important role in maintaining competition in agriculture and allocating resources between agriculture and other sectors of the economy. However, climate change and various shocks such as floods, droughts and environmental degradation have been severely affecting farmers’ livelihoods. This article examines rural household livelihood transition in the context of farm entry and exit decisions in rural Pakistan. We analyzed data for 1867 rural households and brought insights into how livelihood assets, exogenous shocks, climate investment and locational characteristics affect their farm entry and exit decisions. Findings suggest that the proportion of farm entry (24%) was higher than that of farm exit (15%). It was found that ‘crop inputs using as credit’ with a huge markup, crop inputs sold by farmers on net cash in financial crisis, exogenous shocks and poor climate investment are the major factors contributing to farm exit. Probit regressions provided strong evidence that number of working age individuals, land ownership (family farm), livestock ownership, access to canal irrigation and Khal Panchayats system increased the likelihood of farm entry decisions. Farm exit decisions were significantly and positively associated with household migration status, grain food shortage, land ownership (family farm), livestock ownership, water shortage for irrigation during crop seasons, household off-farm income, crop input used as credit, exogenous shocks, distance of household to off-farm source, and lack of local government role in sharing climate knowledge. This study also employed Propensity Score Matching to investigate the impact of entry and exit decisions on households’ well-being in terms of total household income, food security status, and ability to save for emergency funds. It was found that the entry decision significantly increases household income and food security status, while the exit decision significantly reduces household income. These findings provide insights into farm entry and exit for those who are planning livelihood transition, and offer recommendations on how to overcome the constraints faced by farming businesses, agricultural sustainability, self-sufficiency and food security during the transition nationally and internationally.